Sort by

- Relevance
- |Time

... the tank contains 900 kg of water, the z = 0.9 m, so the

**LHS**of EQUATION S is 3/7 of 1 second, 3/7 = 5/7 - 0...2 Answers · Science & Mathematics · 14/03/2012

Hooke's Law for isotropic materials http://www.efunda.com/formulae/solid_mechanics/mat_mechanics/hooke_isotropic.cfm

2 Answers · Science & Mathematics · 07/11/2013

...39;s first find the intersection point of the tangent lines: subtract the

**LHS**of the second eqn from that of the first eqn. 3y + 13 + 3y + 1 = 0 6y...1 Answers · Science & Mathematics · 17/02/2012

..., so the only vertical forces in the cut members in the

**LHS**of the truss are in CG. Then the vertical load in CG...1 Answers · Science & Mathematics · 31/01/2012

(11-2x)/((x+3)(x+1)) dx = dt. Take a integration!!!

2 Answers · Science & Mathematics · 21/01/2012

### Can someone help me solve this? tan s is over 1+cos s + sin s is over 1-cos s = cot s + sec s csc S?

... tan s/(1+cos s )+ sin s/(1-cos s )=cot s+(sec s x csc s)

**LHS**= tan s/(1+cos s )+ sin s/(1-cos s ) (tan s(1-cos s)+sin s(1+cos...1 Answers · Science & Mathematics · 17/01/2012

Put the

**LHS**all in cartesian form and collect common terms, then convert to polar form. ...e. (80-j80). This remove the j term from the denominator. Second part of**LHS**is converted using Re^(jθ)=Rcosθ+jRsin...2 Answers · Science & Mathematics · 25/04/2013

Put the whole left side (

**LHS**) into sines and cosines: tan^2 = sin^2 / cos^2 csc^2 = sin^-2 sec...sin^2 * (sin^2 * cos^2)) / (cos^2 *(cos^2 + sin^2)) cancel the cos^2 and rearrange:**LHS**= (sin^4) / (cos^2 + sin^2) sin^2 + cos^2 = 1, so**LHS**= sin^4 Now...1 Answers · Science & Mathematics · 23/11/2011

To show it to be true for n = k + 1, you have the left hand side equal to 1^2 + 2^2 + ... + k^2 + (k+1)^2 Subbing your assumption for it being true for n = k gives k(k+1)(2k+1)/6 + (k+1)^2 Then the algebra goes as follows: = [k(k+1)(2k+1)/6] + k² + 2k + 1...

1 Answers · Science & Mathematics · 07/11/2011

... to perform it the other way round, i.e. starting from the

**LHS**. A final point is notice that A^2+B^2=R^2((sin^2...1 Answers · Science & Mathematics · 25/04/2013